2016
DOI: 10.4067/s0717-95022016000300004
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Rhododendron Honey on Mice Liver Tissue

Abstract: ILTER, G.; SÖYLER, G.; RASGELE, P. G.; KEKEÇOGLU, M & KAMBUR, M. The effect of rhododendron honey on mice liver tissue. Int. J. Morphol., 34(3): 842-847, 2016. SUMMARY: Rhododendron honey, made by bees from rhododendron pollen, contains a toxic substance called grayanotoxin. Depending on the dose, the poisonous honey can result in serious effects such as cardiac arrhythmia, fibrillation, and myocardial infarction. The purpose of this study is to investigate the effects of the poisonous RH of the Black Sea R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…The 3025-2800 cm -1 region (band No's. [2][3][4][5][6] is called the C-H stretching region and generally provides information about lipids [18] . The 1800-800 cm -1 region (band No's.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3025-2800 cm -1 region (band No's. [2][3][4][5][6] is called the C-H stretching region and generally provides information about lipids [18] . The 1800-800 cm -1 region (band No's.…”
Section: Resultsmentioning
confidence: 99%
“…However, in different regions of the world, this honey is widely used in the treatment of various disorders such as hypertension, gastrointestinal complaints, sexual dysfunction toothache, colds, etc. [2] .…”
Section: Introductionmentioning
confidence: 99%
“…The lack of indication of incidence and severity grade and the absence of biochemical signs of liver toxicity and histopathological data make it difficult to evaluate whether the extent of these changes is significant. Histopathological examinations are available from another study (Kukner et al 2016 ), but no significant increase of incidence in the liver congestion, steatosis and inflammatory cells was observed after 24 h from a single dose of 0.01 mg/kg bw GTX III i.p in mice. Overall, examination of clinical biochemistry parameters and histological observations after GTX I and GTX III administration provided inconsistent data (Fukumoto et al., 1993 ; Ascioglu et al., 2000 ; Silici et al., 2016 ).…”
Section: Assessmentmentioning
confidence: 99%
“…Effects in rodent liver from single‐dose exposure to ‘mad honey’ involved altered lipid/protein ratio and lipid peroxidation (Sibel et al., 2014 ; Eraslan et al., 2018 ; Cakmak‐Arslan et al., 2020a ). Kukner et al ( 2016 ) reported significant congestion and steatosis in the absence of necrosis. The data refer to a single sample of ‘mad honey’.…”
Section: Assessmentmentioning
confidence: 99%
“…Bizim sonuçlarımızla uyumlu olarak, Kükner vd. 2016, DB ve GTX uygulamasından sonra farelerde karaciğer yağlanması meydana geldiğini ışık mikroskopu ile belirlemiştir (15). Önceki çalışmalarda karaciğer yağlanmasının dokuda sadece lipit miktarında artışa değil aynı zamanda glikojen miktarında önemli oranda azalmaya sebep olduğu gösterilmiştir (42,43).…”
unclassified